2015
DOI: 10.1186/s13756-015-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

What roles do accredited drug dispensing outlets in Tanzania play in facilitating access to antimicrobials? Results of a multi-method analysis

Abstract: BackgroundPeople in low-income countries purchase a high proportion of antimicrobials from retail drug shops, both with and without a prescription. Tanzania’s accredited drug dispensing outlet (ADDO) program includes dispenser training, enforcement of standards, and the legal right to sell selected antimicrobials. We assessed the role of ADDOs in facilitating access to antimicrobials.MethodsWe purposively chose four regions, randomly selected three districts and five wards per district. Study methods included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…The TFDA therefore initiated the accredited drug dispensing outlet (ADDO) programme in 2003 to capacitate personnel at Part II pharmacies in the area of essential drug provision [21, 22]. Accredited Part II pharmacies are locally called Duka la Dawa Muhimu and are allowed to dispense some prescription-only drugs such as antimicrobials [22]. In 2013 there were approximately 9000 accredited stores spread across the country [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TFDA therefore initiated the accredited drug dispensing outlet (ADDO) programme in 2003 to capacitate personnel at Part II pharmacies in the area of essential drug provision [21, 22]. Accredited Part II pharmacies are locally called Duka la Dawa Muhimu and are allowed to dispense some prescription-only drugs such as antimicrobials [22]. In 2013 there were approximately 9000 accredited stores spread across the country [22].…”
Section: Methodsmentioning
confidence: 99%
“…Accredited Part II pharmacies are locally called Duka la Dawa Muhimu and are allowed to dispense some prescription-only drugs such as antimicrobials [22]. In 2013 there were approximately 9000 accredited stores spread across the country [22]. …”
Section: Methodsmentioning
confidence: 99%
“…However, current and previous studies have indicated that infringement of policies although reduced, are still very common (Chalker et al, 2015;Goodman et al, 2007). A recent community based study on antimicrobial use among 1,200 household done by Chalker et al (2015) indicated that ADDOs were the more convenient source of medicines by most community members but such sourcing was associated with poor ADDOs dispensing practices and over use or incomplete dosages of antimicrobials in response to incorrect public demand (Chalker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent community based study on antimicrobial use among 1,200 household done by Chalker et al (2015) indicated that ADDOs were the more convenient source of medicines by most community members but such sourcing was associated with poor ADDOs dispensing practices and over use or incomplete dosages of antimicrobials in response to incorrect public demand (Chalker et al, 2015). Inappropriate antimicrobial selling was common, for example, more than one-third of requests by investigators who presented as "mystery shoppers" with acute respiratory infection were approved and also, 85% of prescription-only antimicrobials were sold just on verbal requisition.…”
Section: Introductionmentioning
confidence: 99%
“…Differences existed across regions, but varied by product. For example, in Mbeya antimicrobials in ADDOs were 30% more expensive than in public health facilities, while they were 4% more expensive in public health facilities than ADDOs in Tanga; suspensions in Mbeya were 1% less costly in ADDOs, but 60% more expensive in ADDOs in Morogoro [18]. Using the regimen recommended in Tanzania’s standard treatment guidelines as an illustration [19], the average cost to treat pneumonia in an adult would be TSh444 based on prices of medicines at a health facility (~US$0.26) and TSh528 at an ADDO (~US$0.30) (amoxicillin); and treating a sexually transmitted infection would cost TSh1398 at a health facility (~US$0.81) and TSh1470 at an ADDO (~US$0.85) (benzyl penicillin + co-trimoxazole).…”
Section: Resultsmentioning
confidence: 99%